2006
DOI: 10.1002/em.20231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the SCGE protocol on the amount of basal DNA damage detected in the Mediterranean mussel, Mytilus galloprovincialis

Abstract: Genotoxicity studies using the single cell gel electrophoresis (SCGE) assay indicate that basal levels of DNA strand breaks (SBs) in marine invertebrates are higher and more variable than those in marine vertebrates. This elevated level of DNA damage was attributed to a large number of alkali-labile sites, which are characteristic of the tightly-packaged DNA in invertebrate cells. To investigate if altering the SCGE protocol can artificially modulate high levels of SBs, SCGE experiments were performed on haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Genotoxic biomarkers in sentinel species, are recommended in monitoring investigations and both the Comet assay and the micronucleus test have been largely validated in Mediterranean mussels (Frenzilli et al, 2001;Regoli et al, 2004;Machella et al, 2006;Nigro et al, 2006). In our study, the Comet assay demonstrated a moderate increase of DNA fragmentation in mussels caged to the platform during the first period, further supporting the slight oxidative challenge revealed by antioxidant responses and lysosomal membrane stability.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Genotoxic biomarkers in sentinel species, are recommended in monitoring investigations and both the Comet assay and the micronucleus test have been largely validated in Mediterranean mussels (Frenzilli et al, 2001;Regoli et al, 2004;Machella et al, 2006;Nigro et al, 2006). In our study, the Comet assay demonstrated a moderate increase of DNA fragmentation in mussels caged to the platform during the first period, further supporting the slight oxidative challenge revealed by antioxidant responses and lysosomal membrane stability.…”
Section: Discussionsupporting
confidence: 74%
“…The comet assay was carried out on haemocytes immediately diluted in Ca 2+ /Mg 2+ -free buffer, centrifuged, resuspended in 0.6% low-melting-point agarose, and included in 1% normal-melting-point agarose on glass slides (Machella et al, 2006). Slides were placed into the lysing solution (2.5 M NaCl, 100 mM EDTA, 1% Triton X-100, and 10% DMSO, pH 10, 4°C in the dark for 90 min), and the DNA was unwound in 75 mM NaOH, 10 mM EDTA (pH 13) before the electrophoresis (1 V/cm for 10 min).…”
Section: Analyses Of Genotoxic Effectsmentioning
confidence: 99%
“…Also, seasonal variation and temperature altered both DNA damage baseline levels in untreated animals and cell sensitivity towards environmental pollutants under in vitro conditions (Buschini et al 2003;Hartl et al 2004). The Comet assay detecting DNA strand breaks has demonstrated that higher basal levels of DNA damage are observed in marine invertebrates; hence, the protocol followed in these animals should be considered for biomonitoring the ecogenotoxicity of a region (Machella et al 2006).…”
Section: Comet Assay In Other Bivalvesmentioning
confidence: 99%
“…Haemolymph collected from ten specimens was immediately processed for LMS and DNA integrity. Metallothioneins-like proteins (MTSH), acyl CoA oxidase (AOX), acetylcholinesterase (AChE) and individual antioxidants (CAT, GST, GR, GPx and TGSH) were determined by specific spectrophotometric assays (Bocchetti and Regoli, 2006); TOSC toward peroxyl and hydroxyl radicals by gas chromatographic analyses (Regoli and Winston, 1999); lysosomal membrane stability by neutral red retention time (Lowe and Pipe, 1994); loss of DNA integrity by the comet assay and frequency of micronuclei (Venier et al, 1997;Machella et al, 2006). Data were analyzed by two-way analyses of variance (ANOVA) and principal component analyses (PCA) to test differences between sampling periods and species.…”
mentioning
confidence: 99%